2014
DOI: 10.1007/s00894-014-2412-4
|View full text |Cite
|
Sign up to set email alerts
|

On the chemical behavior of C60 hosting H2O and other isoelectronic neutral molecules

Abstract: The density functional theory (DFT) was used to investigate the chemical behavior of C60 hosting neutral guest molecules (NGM). The deformed atoms in molecules (DAM) allowed identifying the regions of electron density depletion and accumulation. The studied NGM are CH4, NH3, H2O, and HF. Based on dipole moment and polarizabilities analyses it is predicted that the NGM@C60 should be more soluble in polar solvents than C60. The deformations on the surface electron density of the fullerenes explain this finding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
5
16
1
Order By: Relevance
“…The obtained dipole moment is in good agreement with some theoretical estimates 17,18,20 and indicates that shielding by the fullerene cage reduces the dipole moment of HF@C 60 to about 25% of that for isolated HF. 42 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The obtained dipole moment is in good agreement with some theoretical estimates 17,18,20 and indicates that shielding by the fullerene cage reduces the dipole moment of HF@C 60 to about 25% of that for isolated HF. 42 …”
Section: Resultssupporting
confidence: 86%
“…Predictions of the properties of HF@C 60 have been made using classical, 14 semiempirical 15,16 and quantum chemistry techniques. [17][18][19][20] Furthermore it has been postulated that endofullerenes containing freely rotating electric dipoles could exhibit ferroelectricity, due to cooperative alignment of the interacting electric dipole moments. 21…”
mentioning
confidence: 99%
“…Although, such finding may indicate some sensitivity to the external to the fullerene molecular environment, the authors have concluded, 25 on the basis of NMR, FIR and UV/Vis spectroscopic analysis, that the H 2 O molecule is electrochemically stable under the hydrophophic environment inside C 60 . On the other hand, earlier and current electronic structure studies [33][34][35][36][37][38] indicate that the encaged H 2 O molecule is not chemically isolated, and there are significant noncovalent interactions within the cage, causing the elongation of the OH bonds, decrease in the HOH angle, offcenter location of the trapped water molecule, and a notable reduction of the dipole moment of the H 2 O molecule upon confinement in the C 60 cage.…”
Section: Introductionmentioning
confidence: 99%
“…As starting point, we have carried out a DFT calculation with the PW81 functional and the 6 −311+G(d) basis set (1107 contractions), using the geometry reported in Ref. [23]. The corresponding files with geometry and basis set, c60-nh3.ggbs, and with density matrix, c60-nh3.den.gz, are included in the $DAMQT/samples/ Molpro/C60-NH3/ directory to facilitate replication.…”
Section: Performance Testsmentioning
confidence: 99%
“…To mention some recent applications, it has been used in the analysis of electron delocalization and reactivity [17], the rapid topography mapping of density and electrostatic potential [18,19], the investigation of molecular diseases [20], the interpretation of conformers properties in ionic liquids [21,22], and the study of electron distribution in C-60 hosting small molecules [23].…”
Section: Introductionmentioning
confidence: 99%